2020
DOI: 10.7150/ijms.47073
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nomogram Predicting Distant Metastasis in T1 and T2 Gallbladder Cancer: A SEER-based Study

Abstract: Background: Gallbladder cancer (GBC) is the most common malignancy of the biliary system. Early T stage GBC patients with distant metastasis are proven to have a worse prognosis. In this study, our aim was to construct and validate a novel nomogram for predicting distant metastasis in T1 and T2 GBC. Methods: Between 2004 and 2014, patients with T1 and T2 GBC were identified in the Surveillance, Epidemiology, and End Results (SEER) database. All of the eligible patients were randomly divided into training and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…However, nomogram has been applied to predict metastasis in other cancer types. Study by Cai et al combined age, grade, histology, T stage, lymph node metastasis, and tumor size to predict the metastasis in T1 and T2 gallbladder cancer [ 17 ]. In pancreatic ductal adenocarcinoma, demographic and clinicopathological characteristics were used to construct nomogram to evaluate metastasis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, nomogram has been applied to predict metastasis in other cancer types. Study by Cai et al combined age, grade, histology, T stage, lymph node metastasis, and tumor size to predict the metastasis in T1 and T2 gallbladder cancer [ 17 ]. In pancreatic ductal adenocarcinoma, demographic and clinicopathological characteristics were used to construct nomogram to evaluate metastasis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although stage T1 tumors have a shallow depth of infiltration, their outcomes are worse when compared to stage T2 and T3 tumors, and this result is different from the association between the N stage and BM. Cai et al retrospectively analyzed 3,013 patients with gallbladder cancer and concluded that stage T1 has a higher risk of distant metastasis than that associated with stage T2 ( 17 ). Guo et al studied 212,787 patients with colorectal cancer and found that stage T1 is more prone to BM than stages T2, T3, and T4.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the 1-year and 3-year cancer-specific survival rates of non-metastatic GBC were 82.3% and 56.7%, respectively ( 10 ). The GBC with metastasis had a shorter survival time than non-metastatic GBC and was commonly observed in the advanced stage and non-adenocarcinoma type ( 5 ). The three major metastatic pathways of GBC include hematogenous metastasis, lymphatic metastasis, and direct infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous population-based studies investigated that metastasis of lymph nodes and distant organs is prevalent in GBC, with incidence ranging from 17.9% to 64.5% ( 5 , 6 ). The most frequently observed metastatic organs are the liver, lung, and peritoneum ( 7 ).…”
Section: Introductionmentioning
confidence: 99%